THERAPEUTIC CORRELATIONS IN THE AESTHETIC REHABILITATION OF THE FRONTAL AREA: STATISTICAL STUDY ON A GROUP OF PATIENTS FROM NORTH-WEST REGION OF ROMANIA - Mădălina Mihali; Anca Irina Grădinariu; Alina Jehac; Claudia Andreea Nistor; Eliza Drăgan; Petruța Siminiuc; Grigore Dumitru Turda; Kamel Earar (Romanian Dental Association for Education, 2023)
Aim of the study: The present study aims to provide an overview on the problem of restoration of the frontal area, offering alternatives in relation to the technique of performing fixed prosthetic treatments, which adapts according to the etiology of the problem, the patient's expectations, the cost and the possibilities of the medical and technical dental office. Materials and methods: A number of 42 patients from a private practice in Sighetu Marmatiei were analysed during 2021-2023, in terms of need of aesthetic rehabilitation, treatment steps and final result. Clinical charts were filled and analysed for each patient and satisfaction questionnaire was applied and the end of the treatment for 30 of these patients that met the aesthetic criteria analysed in the study. Results and Conclusions:47% of the patients were from the 20-30 age range, from which 67% were female. Treatment was in 66% requested for maxilla, prosthetic restoration being made from ceramic masses. Feldspathic ceramics were used in a rather small percentage of only 8%, while pressed ceramics had a percentage of 46%, equal to that of zirconia-based ceramics. From the study group 40% of patients declared satisfied and the end of the treatment, 40% were elated, and only 7% were dissatisfied by the final results mainly due to the "Hollywood" type of restoration that they envisaged, in disaccord to the natural aspect of the rest of the present teeth on the arches. The restoration of the frontal area is often a challenge for the dentist, who has the mission of keeping the mechanical, biological and aesthetic principles in balance.